Soil-Enzymes and Antioxidants Activities of Edible Vegetables Grown in Soils Polluted by Gas Flaring - Doris Akachukwu,; Paul Ndubuisi Anyiam,; Polycarp Nnacheta Okafor,; Chiedozie Ibegbulem ,; Ifeoma Irene Ijeh, (Tropical Life Sciences Research, 2023)
Associated gas flaring has several consequences on the environment. This study was aimed at assessing the impact of gas flaring on soil enzymes and plant antioxidant activities from gas flare-bearing communities in Nigeria. Soil and plant samples were obtained from farmlands in Ukwa West and Izombe gas flaring sites, as well as unpolluted site from Olokoro (used as control). The level of activities of soil urease, dehydrogenase, phosphatases, plant antioxidant enzymes and lactate dehydrogenase (LDH) of selected plants (Gnetum africanum [GA], Piper guineense [PG], Gongronema latifolium [GL], Pterocarpus mildbraedii [PM]) were evaluated using standard methods. The results showed that the activities of urease were significantly higher (P < 0.05) in soil from Ukwa site than Izombe and the control soil. Dehydrogenase (DHA) and phosphatases recorded higher activities (P < 0.05) for Izombe soil than in Ukwa compared with the control. For plants, superoxide dismutase (SOD), glutathione S-transferase (GST) and glutathione peroxidase (GPx) recorded a significant (P < 0.05) higher activities in all the plants assayed from Ukwa site than Izombe and the control site. The activities of GPx from GA and PG plants at Izombe site were not significant (P > 0.05) when compared with the control, except for PM and GL which recorded a significant decrease (P < 0.05) in GPX and SOD activities, respectively. The activities of catalase enzyme also decreased significantly (P < 0.05) in all plants grown at Ukwa, while an increase was seen for GA and PM grown at Izombe compared with control. The overall variability in enzymes activities is an indication that soil ecosystem and plants are altered significantly by the stress load from the gas flaring pollutants which could serve as bio-indicators for assessing ecological risks and bioremediation.